Selective media as a rapid method for the differentiation of the spoilage yeast Zygosaccharomyces bailii from food and beverages - Schuller, Dorit Elisabeth (1996)
Resumo da comunicação apresentadal no "X Congresso Nacional de Bioquímica", 31.10. - 02.11.1996, Universidade do Minho, Braga, Portugal.